Non-canonical WNT/PCP signalling in cancer: Fzd6 takes centre stage - Corda, G; Sala, A (Springer Nature, 2017)
Frizzled receptors are the mediators of the wnt canonical and non-canonical pathways, which play fundamental roles in cell differentiation and organism development. A large body of work indicates that dysregulation of wnt signalling is a feature of oncogenic transformation, but most of the studies published so far focus on the assessment of the consequences of aberrations of the canonical pathway in human cancer. In this review, we discuss the emerging role of the wnt non-canonical pathway regulated by frizzled receptor 6 (Fzd6) in the pathogenesis of different types of human malignancies. The function played by Fzd6 in the physiology of normal and cancer cells has been highlighted in the view that an increased knowledge of the signalling pathways upstream and downstream of this receptor could ultimately result in the identification of new targets for cancer therapy.